2014
DOI: 10.1155/2014/341529
|View full text |Cite
|
Sign up to set email alerts
|

Humanin Rescues Cultured Rat Cortical Neurons from NMDA-Induced Toxicity Not by NMDA Receptor

Abstract: Excitatory neurotoxicity has been implicated in many pathological situations and there is no effective treatment available. Humanin is a 24-aa peptide cloned from the brain of patients with Alzheimer's disease (AD). In the present study, excitatory toxicity was induced by N-methyl-D-aspartate (NMDA) in primarily cultured rat cortical neurons. MTT assessment, lactate dehydrogenase (LDH) release, and calcein staining were employed to evaluate the protective activity of humanin on NMDA induced toxicity. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 26 publications
(37 reference statements)
0
16
0
Order By: Relevance
“…HN has been shown to protect cultured rat cortical neurons from NMDA-induced neurotoxicity, an effect that seems to be time- and concentration-dependent (Cui et al, 2014, 2017; Yang et al, 2018). In this study, we aimed at studying HN effects on structural synaptic plasticity in glutamate-induced dendritic atrophy and synapse alterations (Podestá et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HN has been shown to protect cultured rat cortical neurons from NMDA-induced neurotoxicity, an effect that seems to be time- and concentration-dependent (Cui et al, 2014, 2017; Yang et al, 2018). In this study, we aimed at studying HN effects on structural synaptic plasticity in glutamate-induced dendritic atrophy and synapse alterations (Podestá et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The rat humanin homolog rattin (HNr) is a 38 amino acid peptide encoded and translated from an open reading frame (ORF) within the mitochondrial 16S ribosomal RNA (rRNA) gene (Caricasole et al, 2002; Paharkova et al, 2015). Several studies have demonstrated that HN is a potent pro-survival factor for neurons exposed to multiple cell stressors, such as Aβ oligomers and over-expression of familial AD-related genes (Hashimoto et al, 2001; Caricasole et al, 2002), serum deprivation (Kariya et al, 2002), stroke (Xu et al, 2006; Gao et al, 2017) and N -methyl-D-aspartate (NMDA)-induced excitotoxicity (Cui et al, 2014). HN and its derivatives have also proven to be beneficial in ameliorating cognitive impairment induced by Aβ, muscarinic receptor antagonists and aging in rodents (Mamiya and Ukai, 2001; Krejcova et al, 2004; Tajima et al, 2005; Niikura et al, 2011; Zhang et al, 2012; Yen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Mamiya et al evaluated the effects of the scopolamine-HBr induced impairment of spontaneous alternation behavior in mice using the Y-maze as an index of short-term memory, and found that HNG reversed the anti-cholinergic drug mediated impairment of the learning and memory function in mice ( 48 ). In a recent publication, Cui et al reported that HN rescued cortical neurons from excitatory toxicity caused by NMDA in a dose-dependent manner without interacting with the receptors, and pointed to the potential role of its use in preventing the damage caused by this pathway ( 81 ). However, studies have shown that HN failed to protect against certain cytotoxicity including Q79, SOD mutants, etoposide, Fas, or basally occurring death indicating specificity in action ( 1 ).…”
Section: Hn and Neurological Diseasesmentioning
confidence: 99%
“…However, HN did not block the intracellular Ca 2+ overload triggered by NMDA. It might induce the reverting of the high Ca 2+ concentration quickly 18. It is still not clear whether HN protects the neurons through attenuation of NMDA-induced mitochondrial dysfunction.…”
Section: Introductionmentioning
confidence: 99%